2003
DOI: 10.1210/en.2002-220606
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Combinatorial Expression of Prolactin and Glycoprotein Hormone α-Subunit Genes by Gonadotropin-Releasing Hormone and Estradiol-17β in Single Rat Pituitary Cells during Aggregate Cell Culture

Abstract: Previously we showed the existence of rat and mouse anterior pituitary cells coexpressing mRNA from two or more hormone genes in which production and/or storage of the corresponding hormones were not detectable. To substantiate a putative function for these cells, we investigated whether these phenotypes were retained during long-term reaggregate cell culture and whether protagonist regulatory factors could expand cell populations expressing particular hormone mRNA combinations. After 4-wk culture and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 57 publications
1
40
1
Order By: Relevance
“…However, those studies that used concentrations of 10 nM or greater most often reported no effects, or even inhibitory effects of estrogen (Fukata and Martin, 1986;Silverman et al, 1988;Hauspie et al, 2003). Our dose-response results agree that higher concentrations of estrogen are not stimulatory and in fact, may inhibit certain aspects of GH gene product expression (Childs et al, 2004).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…However, those studies that used concentrations of 10 nM or greater most often reported no effects, or even inhibitory effects of estrogen (Fukata and Martin, 1986;Silverman et al, 1988;Hauspie et al, 2003). Our dose-response results agree that higher concentrations of estrogen are not stimulatory and in fact, may inhibit certain aspects of GH gene product expression (Childs et al, 2004).…”
supporting
confidence: 76%
“…First, there has been controversy about the presence or types of estrogen receptors on somatotropes (Kikuta et al, 1993;Friend et al, 1994;Shupnik, 2002;Stefanneau et al, 1994;Zafer et al, 1995;Chaidarun et al, 1997;Chaidarun et al,m 1998;Gittoes et al, 1999;Shupnik et al1998;Hal and McDonnell, 1999). Second, not all in vitro studies have demonstrated an estrogen-mediated increase in GH synthesis or secretion (Webb et al, 1983;Simard et al, 1985;Lam et al, 1996;Tulipano et al, 2004;Fukuta and Martin, 1986;Silverman et al, 1988;Hauspie et al, 2003.). In some studies, estrogen has had no effects or inhibitory effects on expression of GH (Fukuta and Martin, 1986;Silverman et al, 1988;Hauspie et al, 2003.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the existence of a cell pool that costores and cosecretes ACTH and TSH during cold stress has been reported (9). Finally, single-cell RT-PCR has also revealed that ϳ30% of pituitary cells display mRNAs for multiple AP hormones (17,(25)(26)(27)(28) in rats, mice, and monkeys. It is remarkable that most of the cells expressing TSH-␤ mRNA (11%) actually costored it with other AP hormone mRNAs (9%), whereas cells expressing only the TSH-␤ mRNA were much less abundant (2%; see Ref.…”
mentioning
confidence: 99%
“…Pregnant rats were sacrificed at E13 and the fetal rats obtained under aseptic conditions. The pituitary was separated under a stereomicroscope and a single cell suspension was prepared and cultured as previously reported [7,8]. Briefly, the isolated pituitary was rinsed with DMEM three times and then cut into small pieces and transferred into DMEM with 0.25% trypsin, 100 μg/ mL streptomycin and 100 U/mL penicillin, and cultured at 37˚C with 5% CO 2 for 30 minutes.…”
Section: Isolation Of Rat Embryonic Pituitary Cellsmentioning
confidence: 99%